Modified icing system containing mint leaf and citrus peel extracts: effects on quality changes and shelf life of Indian mackerel - Viji, P.; Binsi, P. K.; Visnuvinayagam, S.; Ravishankar, C. N.; Venkateshwarlu, G.; Gopal, T. K. S. (Indian Journal of Fisheries, 2016)
The efficacy of ice containing mint (Mentha arvensis) leaf extract (700 mg l-1) and citrus (Citrus aurantium) peel extract (1000 mg l-1) in retarding the biochemical, microbiological and sensory changes in whole Indian mackerel was assessed. Presence of extracts in ice significantly (p